Effect of imperfect bonding on the axisymmetric dynamic response of buried orthotropic cylindrical shells - Dwivedi J.P.; Upadhyay P.C. (My University, 2025)
This paper deals with the dynamic response of an imperfectly bonded buried orthotropic pipeline subjected to p-wave excitation. An infinite cylindrical shell model, including the rotary inertia and shear deformation effects, has been used for the pipeline. Only the axisymmetric response due to an incident compressional wave has been investigated. Effects of imperfect bond between the pipe and the soil have been included by considering a layer of infinitesimally small thickness between the pipe and the soil. The layer possesse stiffness and damping properties against any axial or radial movement. The ddgree of imperfection or the looseness of the bond is incorporated by varying the stiffness and the damping parameters of the layer. Effects of the imperfect bond on the radial and the axial displacement of the shell have been studied in different soil conditions. These effects have been compared with the effects due to changes in the orthotropic parameters of the pipe. © 1989.